Peroxiredoxin‐2 recycling is slower in denser and pediatric sickle cell red cells. Issue 4 (20th March 2022) - Oh, Joo‐Yeun; Bae, Chae Yun; Kasztan, Malgorzata; Pollock, David M.; Russell, Robert T.; Lebensburger, Jeffrey; Patel, Rakesh P.
Abstract: Peroxiredoxin‐2 (Prx‐2) is a critical antioxidant protein in red blood cells (RBC). Prx‐2 is oxidized to a disulfide covalently‐bound dimer by H2 O2, and then reduced back by the NADPH‐dependent thioredoxin—thioredoxin reductase system. The reduction of oxidized Prx‐2 is relatively slow in RBCs. Since Prx‐2 is highly abundant, Prx‐2s' peroxidase catalytic cycle is not considered to be limiting under normal conditions. However, whether Prx‐2 recycling becomes limiting when RBCs are exposed to stress is not known. Using three different model systems characterized by increased oxidative damage to RBCs spanning the physiologic (endogenous RBCs of different ages), therapeutic (cold‐stored RBCs in blood banks) and pathologic (RBCs from sickle cell disease (SCD) patients and humanized SCD mice) spectrum, basal levels of Prx‐2 oxidation and Prx‐2 recycling kinetics after addition of H2 O2 were determined. The reduction of oxidized Prx‐2 was significantly slower in older versuin older versus younger RBCs, in RBCs stored for 4–5 weeks compared to 1 week, and in RBC from pediatric SCD patients compared to RBCs from control non‐SCD patients. Similarly, the rate of Prx‐2 recycling was slower in humanized SCD mice compared to WT mice. Treatment of RBC with carbon monoxide (CO) to limit heme‐peroxidase activity had no effect on Prx‐2 recycling kinetics. Treatment with glucose attenuated slowed Prx‐2 recycling in older RBCs and SCD RBCs, but not stored RBCs. In conclusion, the reduction of oxidized Prx‐2 can be further slowed in RBCs, which may limit the protection afforded by this antioxidant protein in settings associated with erythrocyte stress.